Stable Excitation of Orbital Angular Momentum States in Air-Core Fiber Seeded by an Integrated Optical Vortex Beam Emitter - Jiamin Wang; Jan Markus Baumann; Jing Xu; Karsten Rottwitt; Yunhong Ding (IEEE Photonics Journal)
We experimentally demonstrate excitation of orbital angular momentum states in an air-core fiber by a silicon integrated vortex beam emitter which is designed and fabricated to match the modes supported by the fiber. The coupling loss is measured to be ∼7.5 dB. Excitation of eigenmodes is confirmed by analyzing the fiber output.